(untitled) (Damascus University Journal for legal sciences, 2024)
Women’s work has been and still is one of the topics that has raised controversy in societies throughout the ages. Women’s work has been affected by the different angles from which they are viewed, to evaluate their work and appreciate their role and efforts compared to men’s work, which has prompted the international and local community to develop mechanisms that work to activate the principle of equality between men and women, and not to discriminate against women in the field of work in particular, and in all fields in particular. general. The interest in protecting the rights of working women has led to positive things that cannot be overlooked, the most important of which are the signing of agreements, the issuance of declarations, and the holding of conferences that prevent discrimination against women in all fields, including the field of work, Many national laws concerned with protecting women’s rights have also been issued by all countries and at all levels, and finally activating these rights by monitoring and monitoring their actual application in reality.